Cutaneous findings in fibromyalgia syndrome and their effect on quality of life - Hilal Kaya Erdogan; Senem Sas; Ersoy Acer; Isil Bulur; Ilknur Kivanc Altunay; Hatice Rana Erdem (Wolters Kluwer Medknow Publications, 2016)
Background/Objective: Fibromyalgia syndrome (FMS) is a chronic, generalized pain condition characterized with widespread soft-tissue pain, fatigue, sleep disturbances, and tender points on physical examination. Although, there are numerous articles about the frequency of FMS in dermatologic diseases such as psoriasis and chronic urticaria, few studies have been reported concerning skin findings in FMS. Our objective was to evaluate the skin findings and skin-related symptoms in FMS patients and determine the quality of life in FMS patients with dermatologic diseases. Methods: A total 105 female patients ages between 18 years and 65 years and diagnosed with FMS were included in the study. A total of 105 healthy volunteers were age and sex matched in the control group. Results: Skin related symptoms such as pruritus, burning, tingling, and increased sweating were more common in FMS patients than in the control group. Xerosis, dermographism, lichen simplex chronicus, neurotic excoriations, tinea pedis, and seborrheic dermatitis were more frequent in FMS patients and the differences were statistically significant. Presence of dermatologic disease or skin-related symptoms in FMS patients did not affect the quality life of the FMS patients. Conclusion: Genetic and pathophysiological studies to clarify the relationship between FMS and dermatologic disorders will provide more information on the association and common treatment of these disorders.